ENDOTHELIN-1 ROLE IN HUMAN EYE: A SYSTEMATIC REVIEW - Valerie Gunawan, Alyssa Claudia; Caesari Putri, Aquirina; Zerlinda Purnadi, Natania; Atin, Fulgensius (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Background: Endothelin-1 (ET-1) is a potent vasoactive factor implicated in development of diabetic retinopathy, which is commonly associated with retinal edema and hyperglycemia. Although the vasomotor activity of venules contributes to the regulation of tissue fluid homeostasis, responses of human retinal venules to ET-1 under euglycemia and hyperglycemia remain unknown and the ET-1 receptor subtype corresponding to vasomotor function has not been determined. The aim: This study aims to show endothelin-1 role in human eye. Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2013 and 2023 were taken into account. Several different online reference sources, like Pubmed and SagePub, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: In the PubMed database the results of our search brought up 44 articles, whereas the results of our search on SagePub brought up 95 articles. The results of the search conducted for the last year of 2013 yielded a total 15 articles for PubMed and 42 articles for SagePub. The result from title screening, a total 4 articles for PubMed and 12 articles for SagePub. In the end, we compiled a total of 8 papers. We included five research that met the criteria. Conclusion: ET-1 (vasoconstrictor, mitogenic, pro-oxidative, and proinflammatory) is one of the most potent vasoconstrictors in the body and its action has a dual effect: on the one hand, it acts on receptors of ECs and pericytes; on the other hand, it has a mitogenic effect on VSMCs.